Spectrum of congenital malformations at birth among neonates in a private medical college in South Rajasthan - Bhatia, Ravi; Bhatia, Gunjan (International Journal of Contemporary Pediatrics, 2019)
Background: Congenital anomalies contribute to about 12% neonatal deaths annually .Neonates with multiple congenital malformations pose a very difficult management problem for the treating physician. This study was done to know the incidence, pattern of congenital anomalies and to study various maternal risk factors leading to congenital anomalies which may help us in devising strategies for better patient counseling and management. Methods: Prospective cross sectional study carried out from 1st Jan 2014 to 31st December 2018 in a private medical college in India. Neonates (both live and still born) delivered in our hospital during this period formed the part of study group. All congenital anomalies present were documented and classified according to system involoved. Results: Total number of neonates with congenital anomalies were 90, out of which 73 were live births and 17 were still births. The overall incidence of congenital anomalies was 2.375%. The commonest system affected was musculoskeletal system (27.7%) followed by CNS (24.4%). Among the maternal risk factors studied, increased maternal age, consanguineous marriage, maternal gestational diabetes mellitus were all significant risk factors associated with congenital anomalies. Conclusion: Congenital anomalies are a global health problem. In our study we have documented that multiparity, consanguinity, diabetes mellitus, Pregnancy induced Hypertension (PIH), maternal anemia, maternal malnutrition to be major contributing factors for congenital anomalies. Present study highlighted that musculoskeletal and CNS systems to be the most commonly affected by congenital malformations. Antenatal scans remain an important diagnostic tool in screening for congenital anomalies. A good clinical examination at birth could help in early detection of life threatening congenital malformation thereby improving chances of his or her survival.